PSV-7 Effects of music stimulus on behavior response, cortisol level and immunity horizontal of growing pigs. (30th November 2020) - Li, Jiafang; Han, Qian; Zhang, Runxiang; Liu, Honggui; Li, Xiang; Bao, Jun
Abstract: Enrichment environment is widely used to improve the welfare of domestic animals and satisfy their natural behavior. Music as an enriched environment can reduce abnormal behavior in humans, non-human primates and rodents. The aim of this study was to investigate the effects of repeated music stimuli on the behavior, physiology and immunity of growing pigs. A total of 72 5-week-old hybrid piglets (Large White × Duroc × Minpig) were randomly divided into three treatments groups of the music group (Mozart K.448, 65–70 dB), the noise group (mechanical noise, 85–90 dB) and the control group (silence, less than 40dB). During 60 days of auditory exposure, the behavioral responses, cortisol level and immune horizontal of the piglets were measured. The results showed that the active behavior of the growing pigs increased and lying behavior decreased in the music group compared to the control group (P < 0.05). The music stimulus increased tail wagging, tail in curl and playing behaviors (P < 0.05). The noise stimulus increased aggressive behavior (P < 0.05) but had no effect on the exploring and manipulative behaviors (P > 0.05). The frequency of the event behaviors decreased with the time of auditory stimuli (P < 0.05). Short-term music stimulus had a lower cortisol level than the noise and control groups (P < 0.05). Long-term music stimulus increased the level of IgG, IL-2 and IFN-γ (P < 0.05) and decreased the IL-4 level (P < 0.05). Noise stimulus reduced the level of IgG (P < 0.05) but had no effect on the level of IL-2, IL-4 and IFN-γ (P > 0.05). In conclusion, music stimulus triggers the pigs to show more positive behaviors, and the short-term music stimulus can reduce the stress response, while the long-term music stimulus can enhance the immune responses in the growing pigs.